Periodically Poled Acoustic Wave-Guide and Transducers for Radio-Frequency Applications - Ballandras, Sylvain; Courjon, Emilie; Bassignot, Florent; Ulliac, Gwenn; Hauden, Jérôme; Garcia, Julien; Laroche, Thierry; Daniau, William (IntechOpen, 2011)
None